Method for the hystopathological analysis of the cervix specimen, obtained through radio surgery - Alfredo B. Quiñones Ceballos; Martha María Chávez Valdivia; Caridad Socorro Castro; Ileana Franco Zunda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: Radio-surgery recently introduced in our hospital environment as a method to treat curable malignant lesions of the cervix, constituted a challenge for all the anatomopathologists for the histological distortion it may cause. Objective: To describe a method for the management and interpretation of the biopsy specimen of the neck of the uterus, obtained by radio-surgery. Methods: a flow of coordinated actions was established in the management, on 162 cervix biopsies, from sample taking to final diagnosis during a two years period. Results: This method facilitates the interpretation and topographic location of the lesions, in a way that it clears out the forecasting. It has been evaluated and vouched as satisfactory for its usefulness, easy application, low expense, security, and diagnostic and forecasting confidence.